2021
DOI: 10.1186/s12967-021-03142-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 146a is associated with diabetic complications in type 1 diabetic patients from the EURODIAB PCS

Abstract: Background MicroRNA-146a-5p (miR-146a-5p) is a key regulator of inflammatory processes. Expression of miR-146a-5p is altered in target organs of diabetic complications and deficiency of miR-146a-5p has been implicated in their pathogenesis. We investigated if serum miR-146a-5p levels were independently associated with micro/macrovascular complications of type 1 diabetes (DM1). Methods A nested case–control study from the EURODIAB PCS of 447 DM1 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…Levels of miR-145-5p in the lower tertile were associated with an increased OR for all complications that was predominantly driven by a significantly enhanced risk of both retinopathy and nephropathy. Similarly, we have previously reported that both miR-126 and miR-146-5p were associated with retinopathy and CVD in T1DM patients of the EURODIAB nested case-control study [36,46].…”
Section: Discussionsupporting
confidence: 72%
“…Levels of miR-145-5p in the lower tertile were associated with an increased OR for all complications that was predominantly driven by a significantly enhanced risk of both retinopathy and nephropathy. Similarly, we have previously reported that both miR-126 and miR-146-5p were associated with retinopathy and CVD in T1DM patients of the EURODIAB nested case-control study [36,46].…”
Section: Discussionsupporting
confidence: 72%
“…miR-146a is a key regulator of inflammatory processes. Expression of miR-146a is altered in target organs of diabetic complications, and deficiency of miR-146a has been implicated in their pathogenesis [26]. In human monocytes, miR-146a, which is encoded by the locus of the LOC285628 gene located on chromosome 5, reacts to lipopolysaccharide (LPS) stimulation, and its activation is reliant on nuclear factor kappa B (NF-κB) [27].…”
Section: Biogenesis Of Mir-146amentioning
confidence: 99%
“…Conversely, we previously found that the glomerular miR-146a levels were dramatically reduced in the kidney sections of diabetic patients (18), and that the level of miR-146a expression in the kidneys inversely correlated with proteinuria in the patients, suggesting that podocytic miR-146a plays a protective role in DN. A recent study with 460 subjects (300 cases and 160 controls) also confirmed that there exits an inverse association of blood miR-146a levels with diabetes and its complications (19). Furthermore, miR-146a levels were found to be down-modulated in the kidneys of diabetic rats and mice, suggesting that it plays a reno-protective role (20).…”
Section: Introductionmentioning
confidence: 74%
“…A number of studies, including ours ( 18 ), show that reduced miR-146a levels are associated with injury. For example, serum miR-146a levels inversely and independently correlate with chronic complications of diabetes, including cardiovascular disease (CVD) and diabetic retinopathy, in a cohort of patients with type 1 diabetes ( 19 ). Similarly, serum miR-146a levels show significant age-related decline in type 2 diabetics and show inverse correlation with creatinine ( 40 ).…”
Section: Discussionmentioning
confidence: 99%